Sensitivity-Based Critical Bus Ranking for Available Transfer Capability Assessment of the Nigeria 330 kV Transmission Network under N−1 Contingencies - Ezeonye, Chinonso S; Osuji, Uzoma; Echeme, Tochukwu (Research and Social Study Institute, 2026)
Background: Increasing loadings and recurring contingency of the 330 kV transmission system in Nigeria have led to concerns about voltage stability and available transfer capability (ATC). The determination of these critical buses, which have a great influence on the network performance, is an important issue for planning, operation, and focused reinforcement.Aims and Methods: In this study, a sensitivity oriented approach is developed to rank critical bus and ATC assessment for 330 kV Nigerian grid under N−1 contingency conditions. The framework combines voltage deviation evaluation, ATC calculation, sensitivity ranking, cumulative sensitivity contribution analysis, voltage-ATC coupling evaluation, and post-contingency recovery analysis with a first order exponential model.Result: The findings indicate that system vulnerability is highly location dependent and varies significantly over the network. Bus 22 (Alagbon TS) was identified as the most critical bus with the highest normalised sensitivity index of 1.000 and the most reduction in ATC of 1.65 MW. The cumulative sensitivity analysis showed that the top 15 buses contributed approximately 42% of the total network sensitivity, confirming that vulnerability is concentrated within a relatively small number of locations. The voltage–ATC coupling analysis indicated a strong relationship between the voltage degradation and the transfer capability reduction while the post-contingency recovery assessment proved recovery stability with a recovery time constant of 2.5 s.Conclusion: The proposed sensitivity based approach is used to identify critical buses and to make targeted reinforcement decisions to enhance the reliability and operational security of the Nigeria 330 kV transmission system.